2016
DOI: 10.1039/c6ra13845d
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional ferritin nanocages for bimodal imaging and targeted delivery of doxorubicin into cancer cells

Abstract: Schematic illustration of design of Fe3O4–AFn/DOX–Cdots composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For the purpose of TKIs-loading, commercially purified E. caballus spleen L-subunit-rich FRTs were utilized, with excelling biocompatibility, biodegradability, non-toxicity and high loading efficiency as has been previously demonstrated for a variety of bioactive compounds. 15,17,20,21,[32][33][34] N-PAGE revealed that the FRTs were single protein complex with an apparent MW of about 480 kDa (Figure 2A). Upon pH-dependent reassembly w/o payload, FRTs successfully retained their structural integrity and charge, which is in line with Stuhn et al 35 Similar findings were further obtained for both types of TKIs loading.…”
Section: Physico-chemical Characterization Of Tkis-loaded Frtsmentioning
confidence: 99%
“…For the purpose of TKIs-loading, commercially purified E. caballus spleen L-subunit-rich FRTs were utilized, with excelling biocompatibility, biodegradability, non-toxicity and high loading efficiency as has been previously demonstrated for a variety of bioactive compounds. 15,17,20,21,[32][33][34] N-PAGE revealed that the FRTs were single protein complex with an apparent MW of about 480 kDa (Figure 2A). Upon pH-dependent reassembly w/o payload, FRTs successfully retained their structural integrity and charge, which is in line with Stuhn et al 35 Similar findings were further obtained for both types of TKIs loading.…”
Section: Physico-chemical Characterization Of Tkis-loaded Frtsmentioning
confidence: 99%